Proceedings of sixth International Conference on Soft Computing for Problem Solving : SocProS 2016. Volume 1 - Deep, Kusum; Bansal, Jagdish Chand; Das, Kedar Nath; Lal, Arvind Kumar; Garg, Harish; Nagar, Atulya K.; Pant, Millie, 1979- (Springer, 2017)
This two-volume book gathers the proceedings of the Sixth International Conference on Soft Computing for Problem Solving (SocProS 2016), offering a collection of research papers presented during the conference at Thapar University, Patiala, India. Providing a veritable treasure trove for scientists and researchers working in the field of soft computing, it highlights the latest developments in the broad area of "Computational Intelligence" and explores both theoretical and practical aspects using fuzzy logic, artificial neural networks, evolutionary algorithms, swarm intelligence, soft computing, computational intelligence, etc.
Includes author index.
Keywords: Soft computing -- Congresses.; Problem solving -- Data processing -- Congresses.; elektronické knihy; electronic books